PENERAPAN PRINSIP OBJEKTIVITAS DALAM EVALUASI PEMBELAJARAN SENI TARI DI TINGKAT SEKOLAH MENENGAH - Mairita; Astuti, Fuji; Yuliasma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article examines the urgency of applying the principle of objectivity in the evaluation of dance learning in secondary schools. Objective evaluation is essential to provide an accurate representation of students' abilities, which in turn motivates them to improve their learning performance. Furthermore, objectivity in evaluation helps teachers design and improve the quality of the learning process. This research focuses on identifying the crucial factors that influence the objectivity of evaluation, with the ultimate goal of formulating practical recommendations to strengthen the objectivity of dance learning evaluation. This research uses a literature study approach and field practice analysis to identify challenges and opportunities in applying the principle of objectivity. The results of the study are expected to provide in-depth insights for dance educators, policymakers, and education researchers on effective strategies to improve the quality of evaluation. Thus, this article contributes to the development of a fairer, more transparent, and accountable evaluation system in the context of dance education.